2019
DOI: 10.3390/d12010007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Stressors on Honey Bees (Apis mellifera; Hymenoptera: Apidae): Some Guidance for Research Emerge from a Meta-Analysis

Abstract: Bees play an essential role in plant pollination and their decline is a threat to crop yields and biodiversity sustainability. The causes of their decline have not yet been fully identified, despite the numerous studies that have been carried out, especially on Apis mellifera. This meta-analysis was conducted to identify gaps in the current research and new potential directions for research. The aim of this analysis of 293 international scientific papers was to achieve an inventory of the studied populations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 38 publications
(44 reference statements)
0
16
0
Order By: Relevance
“…When investigating plant protection products, recent attention has mostly been drawn to neonicotinoid insecticides. Fungicides and herbicides are understudied substance classes when it comes to bee health [ 69 , 70 ], as their mode of action does not generally aim to harm insects. Our findings, however, provide evidence that a formulated herbicide can cause sublethal effects at the colony level.…”
Section: Discussionmentioning
confidence: 99%
“…When investigating plant protection products, recent attention has mostly been drawn to neonicotinoid insecticides. Fungicides and herbicides are understudied substance classes when it comes to bee health [ 69 , 70 ], as their mode of action does not generally aim to harm insects. Our findings, however, provide evidence that a formulated herbicide can cause sublethal effects at the colony level.…”
Section: Discussionmentioning
confidence: 99%
“…When investigating plant protection products, recent attention has mostly been drawn to neonicotinoid insecticides. Fungicides and herbicides are currently understudied substance classes in a bee health context (Havard et al 2019, Cullen et al 2019). With regard to our findings, however, we find they deserve closer attention.…”
Section: Discussionmentioning
confidence: 99%
“…Literature searches were conducted from 31 May to 17 June 2019 using Google Scholar and 12–13 August 2020 using Web of Science. Studies were also identified from the citations of three recent review articles and one meta‐analysis on the interactions between pesticides and parasites on the health of Apis mellifera (Collison et al., 2016; Havard et al., 2020; O'Neal et al., 2017; Sánchez‐Bayo et al., 2016).…”
Section: Methodsmentioning
confidence: 99%